Grain size effects on the behavior of silicone rubber high voltage power cables using seagull optimization algorithm - Shaymaa Ahmed Qenwy; Saud Abdulaziz Aldossari; Kareem AboRas; Loai Saad Eldeen Nasrat; Ahmed Hossam-Eldin (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
High voltage insulation is one of the most important components of electrical power systems. Polymeric materials have lately supplanted ceramic materials as insulating materials due to their low weight, straightforward structure, high mechanical strength, good performance in the presence of pollution, ease of transportation, and ability to enhance voltage. The purpose of this thesis is to add micro and nano-sized aluminum oxide (Al2O3) fillers to silicone rubber (SIR) to enhance its electrical characteristics. Micro Al2O3filler with contents of 10wt%, 20wt%, 30wt%, and 40wt% was combined with nano Al2O3with contents of 1wt%, 3wt%, 5wt%, and 7wt% to create samples of SIRcomposites. The composites’dielectric strength is evaluated in a variety of environments, including dry, wet, low-salt wet, and high-salt wet circumstances. In order to boost the insulator’s dielectric strength under diverse environmental conditions, this research aims to develop a weight ratio composition for such a composite. The ideal concentration of nano or micro Al2O3fillers has been calculated using the whale optimization algorithm (WOA) and seagull optimization algorithm (SOA).